THE PROTEOME OF HIGH DENSITY LIPOPROTEIN CHANGES THROUGHOUT GESTATION IN HEALTHY PREGNANCY AND DIFFERS BETWEEN HEALTHY PREGNANCY AND PREECLAMPSIA IN THE THIRD TRIMESTER. (April 2021) - Patanapirunhakit, Patamat; Sulaiman, Wan; Karlsson, Helen; Ljunggren, Stefan; Graham, Delyth; Freeman, Dilys
Abstract : Objective: High-density lipoprotein (HDL) has well-established anti-atherosclerotic properties in the non-pregnant population. HDL may have a potential role in protecting maternal vascular function during pregnancy that fails to occur in preeclampsia. HDL function is determined by its protein and lipid composition. This study aimed to examine protein composition of HDL at different gestations throughout healthy pregnancy and to compare HDL proteome in the third trimester of healthy pregnancy and preeclampsia. Design and method: HDL was isolated from two cohorts of n = 10 healthy pregnant women at 8 different timepoints throughout pregnancy; pre-pregnancy, week 4.6, week 6.1, week 8.4, (cohort 1) and week 15, week 25, week 35 and 3 months post-natal (cohort 2), and from healthy pregnant (n = 10) and preeclampsia (n = 6) women at the third trimester. The proteome of HDL was measured by nano liquid chromatography coupled to tandem mass spectrometry (nLC-MS/MS). Results: There were 16 proteins in HDL that showed significant differences throughout healthy pregnancy which were apolipoprotein A-IV, apolipoprotein C-II, apolipoprotein C-III, apolipoprotein C-IV, apolipoprotein F, apolipoprotein L-I, angiotensinogen, alpha-1-acid glycoprotein 2, alpha-1-antitrypsin, cathelicidin antimicrobial peptide, fibrinogen alpha chain, fibrinogen beta chain, prenylcysteine oxidase 1, serum amyloid a-I, serum paraoxonase/lactonase 3 and vitronectin. In preeclampsia, HDL apolipoprotein A-I was lower than healthy pregnancy, while HDL alpha-1-antitrypsin, pigment epithelium-derived factor and vitamin D-binding protein were higher. Conclusions: There were significant differences in the protein composition of HDL during pregnancy and between healthy pregnancy and preeclampsia in the third trimester. These compositional differences may be involved in HDL function and may indicate HDL's role in vascular protection in pregnancy.